Amphiphilic dipyridinium-phosphotungstate as an efficient and recyclable catalyst for triphasic fatty ester epoxidation and oxidative cleavage with hydrogen peroxide. Issue 12 (12th June 2017) - de la Garza, Luis Carlos; De Oliveira Vigier, Karine; Chatel, Gregory; Moores, Audrey
Abstract : A novel amphiphilic dipyridinium peroxophosphotungstate ion pair achieved remarkable selectivity and recyclability towards epoxidation and oxidative cleavage of fatty acids and esters. Abstract : A novel amphiphilic dipyridinium peroxophosphotungstate ion pair was developed as a selective and recyclable catalyst for the triphasic epoxidation of fatty acids and esters with hydrogen peroxide. The synthesis of the catalyst was studied extensively by solid and liquid phase 31 P nuclear magnetic resonance (NMR). The oxidation of vegetable oils is of prime importance for the production of lubricants, plasticizers, polymer stabilizers and other olefinic compounds. Based on the oxidizing activity of peroxophosphotungstates, we designed a lipophilic phase transfer agent that renders the active complex insoluble in the reaction media, without having to support it on a matrix. This affords a catalyst combining the activity of homogeneous catalysts and the recyclability of heterogeneous systems. We show that this catalyst is able to fully epoxidize methyl oleate with excellent selectivity, with a turnover frequency of 149 at 60 °C, and can be easily recycled, to reach a record turn over number of 1868. A larger scale experiment on 13 grams and a scope including linoleic and ricinoleic acids were also demonstrated. The catalyst also shows excellent activity and selectivity for the oxidative cleavage of methyl oleate and the oxidation of small olefins.